A misericórdia em Jon Sobrino e Walter Kasper : uma abordagem na perspectiva da cultura da paz - Rosa, Darvan Hernandez da (2023)
The present dissertation makes a comparative analysis between two works that deal with the theme of mercy, one of them originating from Latin American theology and the other originating from European theology. Respectively, the first is “The principle of mercy, coming down from the cross to the crucified people” by Jon Sobrino and the second is “Mercy: fundamental condition of the Gospel and key to the Christian life” by Walter Kasper. The inspiration of the theme comes from the pontificate of Francis and, therefore, his main ideas on mercy are evident. The objective of the analysis is, in addition to showing a comparison of the assumptions, methods and content of the works, to establish a dialogue between the two authors on the theme of mercy. This dialogue is enriched by the occasional participation of other authors. From the results obtained from this research, indications are offered for the construction of a culture of peace.